Development of real-time RT-PCR for N2 subtype avian influenza RNA-virus detection - P. B. Akshalova; A. V. Andriyasov; L. O. Scherbakova; S. N. Kolosov; N. G. Zinyakov; I. A. Chvala; D. B. Andreychuk (Ветеринария сегодня)
Currently, N2 subtype avian influenza (AI) virus actively circulates in domestic and wild bird populations and is regularly detected in China, other Asian countries and Russia, particularly in combination with H9 hemagglutinin. Therefore, a method for rapid detection of the said infectious agent is urgently required. Data on oligonucleotide primer selection and reverse transcription real-time polymerase chain reaction condition optimization for N2 AI virus detection are presented in the paper. Modified primers and probe proposed by B. Hoffmann in 2006 as well as original primers and probes with the viruses available in the Laboratory working collection and selected during testing were assessed for N2 neuraminidase gene fragment amplification. Optimal concentrations of real-time RT-PCR master mix components and temperature-time mode were determined. Various combinations of primers were tested against ten N2 avian influenza virus isolates that genetically differed from each other in N gene. Nine viruses were isolated from birds in the Russian Federation regions and classified to different genetic groups. The real-time RT-PCR assay was tested for its specificity using AI virus isolates of different neuraminidase subtypes (H5N8, H3N6, H4N6, H5N1, H10N7) as well as samples containing other RNA-viruses: Newcastle disease virus, infectious bronchitis virus and infectious bursal disease virus. As a result of the testing, real-time RT-PCR conditions providing high sensitivity and specificity of the assay were selected and optimized.